2022
DOI: 10.1177/09500170221083106
|View full text |Cite
|
Sign up to set email alerts
|

Recoupling Corporate Culture with New Political Discourse in China’s Platform Economy: The Case of Alibaba

Abstract: Previous research on the corporate culture construction in China primarily highlights how Chinese firms draw on its traditional culture and socialist heritages as two crucial intellectual resources. The highly marketised high-tech sector with declining employment security and changing political environment renders a new context and dual process for the ‘engineering’ of corporate culture in China’s platform economy. An ethnographic study of Alibaba unveils the resources the management draws on to construct its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…This suggests that Ant Forest’s two main game design strategies—the concept of environmental protection and the popularization of green carbon finance knowledge—do not seem to have a real effect, that is to say, to generate positive environmental engagement among users to demonstrate their motivation and satisfaction to participate in online public welfare projects [ 17 , 78 ]. In addition, among Ant Forest users, the qualitative results show that some users realize the importance of environmental protection and the sense of honor brought by Ant Forest, and, due to the expression of their value, are more motivated to use it, which is consistent with the findings of some previous studies [ 79 , 80 ]. The results show that the motivation of Ant Forest users had a significant positive impact on their satisfaction.…”
Section: Discussionsupporting
confidence: 88%
“…This suggests that Ant Forest’s two main game design strategies—the concept of environmental protection and the popularization of green carbon finance knowledge—do not seem to have a real effect, that is to say, to generate positive environmental engagement among users to demonstrate their motivation and satisfaction to participate in online public welfare projects [ 17 , 78 ]. In addition, among Ant Forest users, the qualitative results show that some users realize the importance of environmental protection and the sense of honor brought by Ant Forest, and, due to the expression of their value, are more motivated to use it, which is consistent with the findings of some previous studies [ 79 , 80 ]. The results show that the motivation of Ant Forest users had a significant positive impact on their satisfaction.…”
Section: Discussionsupporting
confidence: 88%
“…The informants suggested that EPFs commonly promoted a corporate culture and management system, perpetuating the anxiety over career security and development and prioritising the corporate objectives and control (Tse & Li, 2022; Yan, 2021). The tasks and competition faced by graduates were usually described as ‘challenging the limit’ (Jorge, Senior asset manager), ‘harsh and cruel’ (Larry, Investment banker) and ‘energy‐consuming’ (George, Consulting manager).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have revealed that professional firms in China have increasingly adopted a market‐oriented corporate culture and managerial system, which incites market competition and meritocracy (Tse & Li, 2022), promotes the discourse of ‘self as an enterprise’ (Yan, 2021) and enhances ‘meticulous management’ over professionals (Zhuang & Han, 2021). Combining with other conventional features of the Chinese workplace, such as the emphasis on hierarchy and conformity (Wang, 2020), this heightened control over the professional labour process has intensified daily workload, performance assessment and peer competition, thereby undermining the sense of job security and autonomy (Yan, 2021; Zhuang & Han, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, why and how these workers have actively built the link between their internal psychological factors and the wider external structures have not yet been fully considered and categorised empirically. These external structures include the environmental context (namely global competition, marketisation and digitisation; Hassard and Morris, 2018; McDonald, 2018); institutional and organisational characteristics (such as management efficiency, permeable hierarchies and organisational culture; Alberti et al, 2018; Tse and Li, 2022); modes of creative production and consumption (Campbell et al, 2019); sociocultural factors (Alacovska and Gill, 2019); employment relationships and the roles and impacts of multiple actors (Tomlinson et al, 2018) within specific sectors. Taking these ideas to their logical conclusion would also imply that each site of investigation represents both universal etic behaviours and culture-and-context-dependent emic features.…”
Section: ‘Northern’ Creative Labour Studies and Their Limitsmentioning
confidence: 99%